If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(h + -4) = 6h + 4 Reorder the terms: 6(-4 + h) = 6h + 4 (-4 * 6 + h * 6) = 6h + 4 (-24 + 6h) = 6h + 4 Reorder the terms: -24 + 6h = 4 + 6h Add '-6h' to each side of the equation. -24 + 6h + -6h = 4 + 6h + -6h Combine like terms: 6h + -6h = 0 -24 + 0 = 4 + 6h + -6h -24 = 4 + 6h + -6h Combine like terms: 6h + -6h = 0 -24 = 4 + 0 -24 = 4 Solving -24 = 4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(x-2)=-18 | | 7-2(6z+8)=-9(z+6)+3 | | 1.6h-72=-4h-30 | | 30=x+3 | | 5y+2=4y+10 | | 3-4=2x+5 | | 3-6(-7y-4)=(-4y+8)-7 | | 3-4=2x-5 | | 4x+2-5y=7-6y | | .5n+5=3 | | 50.00+12.00s= | | c/3+c/6 | | 7(x+9)=7x-9 | | 80=9/5c+32 | | 3m+1=16 | | q=2p+8*p | | -1-2x=5x-71 | | x^2+-6= | | 6x^2+48=-12x | | -(-4-2r)=6.5-.5r | | 2975-500=440x | | 1/2q=9-2/5q | | 8-11x=3x+369 | | 8.39=x+.15x | | 5c+6=-9 | | 7(x+1)=7x-9 | | q=2p+8forp | | 2(1/3k-6)^2+(5/3k-6)+2=0 | | x^2-2x-3/4=0 | | 2/5m=1/3(2m-12) | | 4.9x^2+4x+3=0 | | 3=x+7-1 |